POLYMYXIN-SEWN HEMOSORBENT FOR THE TREATMENT OF PATIENTS WITH SEPTIC SHOCK - V. V. Kirkovsky; I. G. Kolesnikova; D. S. Tretyak; E. L. Sedjolkina (Неотложная медицинская помощь)
ABSTRACT. The key component of the sepsis pathogenesis is the gram-negative bacteria endotoxin. It is a lipopolysaccharide of the bacterial wall, which circulation in the bloodstream results in unlimited activation of some biological systems, causing serious complications. Nowadays, there are developed and practiced sorption methods, based on the selective removal of the lipopolysaccharide from the blood during perfusion through the sorption column with covalently immobilized polymyxin on a bioinert matrix, which can bind and inactivate it. The therapeutic effect of hemosorption using the biospecific antilipopolysaccharide hemosorbent has been studied in patients with septic shock, associated with peritonitis and septic complications of destructive pancreatitis.